The Cassette: Documentary Film About Music and Personal Transformation - Zachary Fernandez (2022)
This master thesis is a reflection paper that is a reference to the work that has been accomplished in the development of my master thesis film “The Cassette: Documentary film about music and personal transformation”. The film addresses the personal connection to music and the emotional psyche that assists in the transformation and development of individuals striving to become musicians and artists. To explain this topic, I produced, directed, and edited a film about my own personal connection to music and seamlessly connected my story with another accomplished musician’s story. This established emotional connection is at the same time a method of persuasion. The main finding was the fact that it is best to understand during the early development phase of the film what the possible physical or auditoral emotional connection of the audience with the subject of the film is. The research also addresses the importance of feedback at any development stage of the film as an opportunity for growth and improvement.